Vanadium and titanium extraction from titaniferous slag using a roast-leach process - Nkosi, Sanele (Department of Chemical Engineering, 2026)
Vanadium (V) is typically extracted from the titaniferous magnetite (titanomagnetite) ore using either the V primary production and V and steel co-production process. The V primary production process is the roast-leach process which involves roasting, leaching, precipitation, and calcination of the titanomagnetite. The V and steel co-production process entails the smelting of titanomagnetite in the presence or absence of the fluxes. In the presence of flux i.e. the fluxed smelting approach, most of the V reports to the pig iron, whilst titania (TiO2) reports the slag. This slag is discarded since the TiO2 grade is considered too low for upgrading. Also, this titaniferous slag has a complex phase chemistry such that the spinel and pseudobrookite solid solution (ss) phase incorporate most of the V and Ti species. The objective of this project was to investigate a roast-leach process that would maximize the extraction of V from the titaniferous slag and remove high amounts of impurities from the water leach residue to maximize the TiO2 grade in the product residue. The slag produced by the now-defunct EVRAZ Highveld Steel and Vanadium Cooperation (EHSV) of South Africa (SA) was used as a case study. The EHSV titaniferous slag contains about 0.9% V2O5 and 35.6% TiO2. The best roasting conditions were investigated through the variation of Na2CO3: NaOH ratios, stoichiometric Na additions, roasting temperatures, roasting times, particle size distribution (PSD), and Na reagents i.e. Na2CO3, NaOH, and Na2SO4 salts. The roasting stage is aimed at the conversion of V2O5 in the titaniferous slag to a water soluble sodium metavanadate (NaVO3). The produced roast products were leached using water at standard conditions of 70°C, 120 minutes leaching time, s:l ratio of 1:4, and agitation speed of 350 rpm. The produced water leach residue was further subjected to acid leaching using HCl as a lixiviant with 20% acid concentration, at 110°C, 24 hours, s:l ratio of 1:4, and agitation speed of 350 rpm. The acid leaching stage was conducted in order to remove impurities such as Al, Ca, Mg, and Fe. The resulting acid leach residue was further upgraded through caustic leaching for Si impurity removal. The standard caustic leaching conditions that were used include 2.15 M NaOH solution as a lixiviant, leaching temperature of 100°C, leaching time of 3 hours, s:l ratio of 1:4, and agitation speed of 350 rpm. The best roasting conditions were used to measure the best leaching conditions by variation of the leaching time from 1 to 24 hours and acid concentration from 15% to 25%. The residue from the best leaching conditions were subjected to standard caustic leaching conditions. The high TiO2 grade that resulted from the removal of impurities was washed to remove the Na present in the residue. The best roasting conditions were 200% stoichiometric Na addition of Na2CO3: NaOH ratio of 100:0 and 0:100, 1000°C, 120 minutes, PSD of -850+105 μm. The best V extractions of 75.7% and 73.7% were attained when 200% stoichiometric Na2CO3 and NaOH were used respectively. Na2CO3 salt was the reagent that was used for downstream upgrading of the water-leach residue since it is cheap and used in industrial operations. The TiO2 grade of 68.7% was attained in the caustic-leach residue when the best roasting conditions were used for roasting the titaniferous slag. The phase composition results showed that pseudobrookite ss and the spinel do decompose when excess Na was added. After this decomposition, the SEM showed that the Na3MgAlSi2O8 phase forms after roasting. This phase also decomposed during water leaching to form the Na2MgTi2O6 phase which contains high Ti and Si species and several impurities. Acid leaching results showed the possibility of minimising Mg, Ca, and Fe impurities. Al impurities in the acid-leach residue remained high in concentration. The phase composition results showed that Al species were present in all the phases that formed after acid-leaching. The caustic leaching process was a success since most of the Si impurities were removed. The phase composition results showed that the minor Si species present in the caustic-leach residue were in the rutile phase. The produced caustic-leach residue still contained several impurities. The best leaching conditions were 24 hours leaching time and 25% HCl lixiviant concentration. Using these best conditions resulted in TiO2 grades of 71% in the caustic leach residue. Washing of this caustic leach residue further increased the TiO2 grade to 79.6%. The phase composition of the washed sample showed that the concentration of Na and Si impurities in the residue decreased. The rutile phase also contained a variety of Mg, Al, Cl, and Ca impurities. The impurity extraction degrees showed an increase with increasing leaching time. The extraction degrees followed the order of Mg > Fe > Al > Ca when leaching times were varied. The R2 values of Mg and Fe showed that the rate controlling mechanism is the surface chemical reaction whilst Al and Ca are controlled by diffusion across product layer and interface transfer. The evaluation of V and impurity extraction from the titaniferous slag was possible at the attained best conditions. The impurities were not fully removed to their maximum, hence the high TiO2 grade product was still contaminated with impurities. The produced TiO2 grade did not meet the TiO2 feedstock specifications as the MgO, CaO, Al2O3, and FeO impurities were still high in the final product, therefore further optimization work is required.